Ethical Implications of AI-Driven Recruitment: A Multi-Perspective Study on Bias and Transparency in Digital Hiring Platforms - musrifah, Fadlul; Hasanah, Ika Ariani (Journal of Management and Informatics, 2025)
Integrating Artificial Intelligence (AI) into digital recruitment platforms has introduced significant enhancements in efficiency and decision-making, alongside complex ethical challenges regarding fairness, transparency, and accountability in candidate evaluation. This study investigates how leading AI-driven recruitment platforms articulate and operationalize ethical principles and whether these commitments are effectively translated into practice. Employing a qualitative exploratory design, the research analyzes official white papers, privacy policies, and AI ethics statements from LinkedIn, HireVue, Pymetrics, and ModernHire. Data was examined using AI-assisted text mining and thematic content analysis to identify ethical discourse patterns and assess the depth of implementation. The findings indicate that moral terms such as “fairness” and “bias” are cited frequently, with LinkedIn referencing them 27 times and HireVue 19 times. A comparative transparency assessment yielded scores of 8.5 out of 10 for LinkedIn, 7.2 for HireVue, 6.8 for Pymetrics, and 4.3 for ModernHire, while formal mechanisms for candidate appeals were absent on most platforms. This study contributes to the field by revealing a persistent gap between stated ethical ideals and operational practices in AI recruitment and by recommending the adoption of explainable AI, transparent auditing frameworks, and international regulatory standards. Such measures are essential to foster more accountable, equitable, and humane AI-based hiring processes.